Pengaruh Temperatur dan Tebal Lapisan Susu Kedelai pada Tray dalam Pengeringan Busa terhadap Kualitas Susu Kedelai Bubuk - Anita Dwi Pratiwi (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The making of soy milk powder with foam drying methods is one of the product innovation effort which it can produce commercially by small industry and also home industry in Indonesia. The purpose of this research was to study the effect of drying temperature and soy milk foam thickness on the tray against the soy milk powder making process using the tray dryers. In this research, added coconut oil, dextrin and tween 80 are added to the soy milk for optimalized that drying process. Tween 80 ((Polyethylene Sorbitan Monoelat ) and dextrin interacted each other, tween 80 act as foam maker, while dextrin act as foam stabilizer during drying process. Coconut oil as heat conductor so that can increasing drying rate. The benefit of this research is to develop the industrial milk powder in small and medium industries. The method used is a variations in temperature drying is done at a temperature of 50°C, 60°C, 65°C, and 70°C with a thickness of soy milk made at 1mm, 2mm, and 3mm. Pressure drying operation remains at 690 mmHg. The results showed that the higher the temperature of drying the moisture content decreases while the thicker layer of soy milk then the water content will be greater. Soy milk powder that has met the SNI moisture content of 4.61%, 23.37% protein content and fat content of 22.94% contained at a temperature of 50 ° C with a 1 mm thick.